The Influence of Promotion, Price and Brand Image on Impulse Buying with Hedonic Shopping Motivation as Intervening Variable - Sandra aulia Kusumawardhani; Alugoro Mulyowahyudi (Sultan Publisher, 2023)
This study aims to determine impulse purchases when shopping on the Shopee platform. The purpose of this research is to analyze the relationship between impulsive buying, with independent promotion variables, price, brand image and hedonic shopping motivation as intervention variables. This study uses a quantitative approach in the form of a survey method. The population in this study consisted of Shoppe users who shopped more than 2 times throughout Indonesia. The sample in this study consisted of 147 Shopee users. Data processing is carried out using the Partial Least Square (PLS) method. The results of this study indicate that price and brand image have a positive and significant effect on hedonic shopping motivation while promotions have a positive and insignificant effect. The influence of brand image and hedonic shopping motivation has a positive and significant effect on impulsive purchases, while promotions and prices have a positive and insignificant effect. The effect of price and brand image has a positive and significant effect on impulsive purchases through hedonic shopping motivation while promotion has a positive and insignificant effect.